Violências e desafios no empreendedorismo de mulheres - Fabrício, Joiceli dos Santos (2021)
The role that women have played in the Brazilian and global entrepreneurial field is increasingly relevant. However, there is an insufficiency in mainstream studies to adequately portray the issue of gender relations to which entrepreneurial women are exposed. This is because we must consider that the practice of entrepreneurship is also mediated by the same tension of gender relations established by the traditional roles of society. Therefore, this thesis aims to analyze which challenges and violence were experienced from the narratives of the participants of the Grupo Mulheres Empreendedoras de Guarapuava. The reference is based on the “absences” of the discussion about gender in the field of female entrepreneurship, in which it is currently treated only as a binary category, the contribution of feminist theory, as well as the contributions of Joan Scott, Hanna Arendt and Michel Foucault. We understand that it is necessary and urgent to problematize female entrepreneurship in its essence: the historical inequality between men and women, giving it a resignification that incorporates its problematization. As for the design of the methodological procedures, this was a qualitative study of an interpretive nature, that is, we consider the aspects of subjectivity as fundamental elements in the subjects' notion of reality and, consequently, in the social dimension. In this sense, because I am also a woman and an entrepreneur, we perceive ourselves as a researcher and as a research subject at the same time, and we start with an autoethnographic reflection, as a step to deepen the questions raised in the field. A further 14 interviews were carried out, analyzed through narrative research. Based on the theoretical construction and empirical reference, our answer to this theoretical gap is inspired by Scott (1995) and proposes the resignification of the construct called “resignified female entrepreneurship”, starting to consider the asymmetry of power, violence and machismo that the woman faces when creating and maintaining her business. The research showed that the narratives of the lived experiences reveal an additional difficulty to the entrepreneurship practiced by these women, considering that they are socioculturally conditioned to overload themselves to handle so many activities. The reports also point to a continuum of violence and challenges: explicit violence, perceived violence in entrepreneurial practice and symbolic violence, suffered and practiced. Through narratives, we had access to cases that almost had a tragic outcome. Symbolic violence permeates the daily lives of female entrepreneurs, and some do not realize, or naturalize, these situations of male domination.